2010
DOI: 10.3945/ajcn.2010.29847
|View full text |Cite
|
Sign up to set email alerts
|

Body composition assessed by the 4-component model and association with lung function in 6–12-y-old children with cystic fibrosis

Abstract: Background: Malnutrition is an indicator of a poor prognosis in patients with cystic fibrosis (CF). Previous body-composition (BC) studies in children with CF used 2-component models (2CMs) to assess fat mass (FM) and fat-free mass (FFM), but to our knowledge no study has used the gold-standard 4-component model (4CM), which allows for a more accurate evaluation of the nature of both elements. Objective: We measured BC by using the 4CM in 6-12-y-old children with CF to 1) compare findings with those of healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 54 publications
(60 reference statements)
2
26
1
Order By: Relevance
“…To our knowledge, the inverse relationship between adiposity and lung function has not previously been described in CF. Additional body composition studies in CF have reported either no relationship 21,22 or a positive relationship 23 between adiposity and lung function, although previous studies have focused on younger aged subjects compared to our cohort. The negative associations of excess adiposity on lung function have been described in the non-CF literature 8,9,24 and may reflect a restrictive mass loading effect on the thorax and upper abdomen created by adipose tissue accumulation, pro-inflammatory effects of adipose tissue, and/or general physical deconditioning 24 .…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…To our knowledge, the inverse relationship between adiposity and lung function has not previously been described in CF. Additional body composition studies in CF have reported either no relationship 21,22 or a positive relationship 23 between adiposity and lung function, although previous studies have focused on younger aged subjects compared to our cohort. The negative associations of excess adiposity on lung function have been described in the non-CF literature 8,9,24 and may reflect a restrictive mass loading effect on the thorax and upper abdomen created by adipose tissue accumulation, pro-inflammatory effects of adipose tissue, and/or general physical deconditioning 24 .…”
Section: Discussioncontrasting
confidence: 55%
“…However, air displacement plethysmography is based on the two-component model of body composition which partitions body weight into fat mass and fat-free mass and is dependent on the assumption that the density of fat-free mass is constant, regardless of age, sex, race, or disease state 31 . Future studies using the four-component model in adult CF, which partitions body weight into fat, water, mineral, and protein, will be of interest to more accurately quantify body composition in CF 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Some obese children are too large to be successfully scanned by DXA and are difficult to measure by using skinfold-thickness calipers but can undergo plethysmography (42). When hydration varies beyond the normal range, and when patients are able to undergo a wider range of measurements, the 4C model is ideal, as we have shown for obesity (29), acute lymphoblastic leukemia (30), and cystic fibrosis (43). Thus, our reference data should substantially increase the capacity of clinicians to acquire and interpret data in a wide range of diseases, which could contribute to a range of components of clinical management.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, DXA-derived LBM, which estimates non-bone LBM, was correlated with degree of lung function impairment in adults and with clinical severity score in both children and adults in studies with small sample sizes (7, 13). In contrast, Williams et al (14) studied body composition in 6- to 12-year-olds with PI-CF using a four-compartment model, a technique limited to the research setting. Their study found that girls with PI-CF had a significantly lower fat mass (FM) compared to age-, height-, and puberty-matched controls, and that FM was positively associated with FEV 1 %-predicted.…”
Section: Introductionmentioning
confidence: 99%